(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
This article discusses the possibilities of making a cinema with the mobile phone through the exposure of the most relevant cases of feature films made with mobile phones in recent years. This technology has undergone changes of such caliber that today it is presented as a very interesting alternative to the conventional camera. And it is in independent cinema, where it promises to obtain its greatest development in the coming years, being able to consolidate, soon, as a new option to film and distribute films through conventional screens or those of the own devices.